2010
DOI: 10.1103/physrevb.81.224439
|View full text |Cite
|
Sign up to set email alerts
|

Shape and strain-induced magnetization reorientation and magnetic anisotropy in thin film Ti/CoCrPt/Ti lines and rings

Abstract: The contributions to the magnetic anisotropy of thin-film rings and lines of width 50 nm and above made from Ti͑5 nm͒ / Co 0.66 Cr 0.22 Pt 0.12 ͑10 and 20 nm͒/Ti ͑3 nm͒ with a perpendicular magnetocrystalline anisotropy are investigated, using magnetic force microscopy to image the ac-demagnetized state. Four regimes of behavior were observed in both lines and rings. Samples with the largest widths ͑Ͼ500 nm͒ showed an out-ofplane maze domain structure typical of unpatterned films with domain widths of ϳ200 nm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…Stripe domains were present, typical of systems with perpendicular magnetic anisotropy. From the self-correlation transform of the MFM image [49], an estimation of the average domain size was ≈(180 ± 10) nm [50]. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stripe domains were present, typical of systems with perpendicular magnetic anisotropy. From the self-correlation transform of the MFM image [49], an estimation of the average domain size was ≈(180 ± 10) nm [50]. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6(b) shows α(T ) for Ni, Al, and Al 2 O 3 and, although, for T > 200 K, α(T ) exhibits a fairly linear trend, a tendency toward a constant value is seen as we lower the temperature. The upper limit of the temperature-dependent strain [ε(T )] exercised by the Al on the Ni NWs is then given by the mismatch between α Al and α Al 2 O 3 , and can be calculated by 12,13,42 Considering that the NWs are subjected to an in-plane biaxial strain, 43 the axial stress (σ ax ) is then obtained from…”
Section: B Contribution From the Magnetoelastic Anisotropymentioning
confidence: 99%
“…In prior works, we showed that the hysteresis loops of both 10-and 20-nm-thick CoCrPt thin films had out-of-plane remanence ratio ≈ 1, and an in-plane hard axis [28,29]. MFM of ac-demagnetized 20-nm-thick CoCrPt films showed a maze domain structure, typical of thin films with out-of-plane anisotropy, and with an average domain size of (180 ± 10) nm [28,30] (the 10-nm film could not be imaged since the stray field of the MFM tip significantly modified the domain patterns). Moreover, using MFM, polarized neutron reflectometry, and micromagnetic simulations, we determined that while the domain walls in 20-nm-thick CoCrPt films consist of a Bloch wall in the center of the thin film with a pair of Néel caps at the surfaces, the 10-nm-thick film exhibits pure Bloch walls [28].…”
Section: Introductionmentioning
confidence: 78%